Commercial strain-derived clinical Saccharomyces cerevisiae can evolve new phenotypes without higher pathogenicity - Pfliegler Valter Péter; Boros Enikő; Pázmándi Kitti Linda; Jakab Ágnes; Zsuga Imre; Kovács Renátó; Zsoldiné Urbán Edit; Antunovics Zsuzsa; Bácsi Attila; Sipiczki Mátyás; Majoros László; Pócsi István (Wiley, 2017)
Scope: Saccharomyces cerevisiae is one of the most important microbes in food industry, but there is growing evidence on its potential pathogenicity as well. Its status as a member of human mycobiome is still not fully understood.Methods and results: In this study, we characterise clinical S. cerevisiae isolates from Hungarian hospitals along with commercial baking and probiotic strains, and determine their phenotypic parameters, virulence factors, interactions with human macrophages, and pathogenicity. Four of the clinical isolates could be traced back to commercial strains based on genetic fingerprinting. Our observations indicate that the commercial-derived clinical isolates have evolved new phenotypes and show similar, or in two cases, significantly decreased pathogenicity. Furthermore, immunological experiments revealed that the variability in human primary macrophage activation after co-incubation with yeasts is largely donor- and not isolate-dependent.Conclusion: Isolates in this study offer an interesting insight into the potential microevolution of probiotic and food strains in human hosts. These commensal yeasts display various changes in their phenotypes, indicating that the colonization of the host does not necessarily impose a selective pressure towards higher virulence/pathogenicity.